Analisis Kepemimpinan Dalam Pembinaan Koperasi Pada Dinas Koperasi dan UKM Kota Prabumulih - Welamsyah, Welamsyah; Putra, Raniasa; Wulandari, Novita (Journal of Law & Policy Review, 2023)
This article or writing aims to analyze what factors influence leadership towards cooperative development at the Prabumulih City Cooperatives and SMEs Service and to analyze leadership towards cooperative development at the Prabumulih City Cooperatives and SMEs Service, as well. Data was collected through interviews, observation, and documentation, while data analysis techniques used interactive analysis techniques. The research results show that leadership in cooperative development at the Prabumulih City Cooperative and SME Department faces various challenges, including low member awareness, lack of participation, difficulty enforcing discipline, lack of entrepreneurial spirit, inadequate regulations, complex bureaucracy, limited access to funds, less effective marketing, and licensing constraints. Strategic steps are needed from local governments, supporting organizations, and cooperative members to support the growth of cooperatives as pillars of a strong local economy. Cooperative development needs to strengthen education and training, focus on management, capital and action research, as well as improve collaboration with external stakeholders to support small food processing businesses in Prabumulih City.